Interleukin-1 beta and interleukin-8 in healthy and inflamed dental pulps - Alessandra Cecília Oliveira Silva; Miriam Rubio Faria; Alexandra Fontes; Marcia Sampaio Campos; Bruno Neves Cavalcanti (University of São Paulo, 2009)
After aggression to the dental pulp, some cells produce cytokines in order to start and control the inflammatory process. Among these cytokines, interleukin-1 beta (IL-1β) and interleukin-8 (IL-8) emerge as important ones. OBJECTIVE: The purpose of this study was to analyze the location, distribution and concentration of these cytokines in healthy and inflamed dental pulps. MATERIAL AND METHODS: Twenty pulps, obtained from healthy third molars (n=10) and from pulpectomies (n=10) were used for the study, with half of each group used for immunohistochemistry and half for protein extraction and ELISA assays. Fibroblasts obtained from healthy dental pulps, stimulated or not by Escherichia coli lipopolysaccharide (LPS), in order to simulate aggression on the cell cultures, were also used and analyzed by ELISA for IL-1β and IL-8 as complementary information. Data obtained from immunohistochemistry were qualitatively analyzed. Data obtained from ELISA assays (tissue and cells) were statistically treated by the t-test (p<0.05). RESULTS: Immunohistochemically, it was observed that inflamed pulps were strongly stained for both cytokines in inflammatory cells, while healthy pulps were not immunolabeled. ELISA from tissues quantitatively confirmed the higher presence of both cytokines. Additionally, cultured pulp fibroblasts stimulated by LPS also produce more cytokines than the control cells. CONCLUSIONS: It may be concluded that inflamed pulps present higher amounts of IL-1β and IL-8 than healthy pulps and that pulp fibroblasts stimulated by bacterial LPS produce higher levels of IL-1β and IL-8 than the control group.